Urban development and peri-urbanization in the Hodna Region. Fragmentation of urban space; City of M’sila - Zohra, Oudina Fatima; Khalfallah, Boudjemaa (Technium Social Sciences Journal, 2023)
The shift and changes that are happening in the world—and Algeria in particular—is rooted in urban existence. The significant changes in social structures and lifestyles have resulted in rapid, vast, and even violent urbanisation during the past few decades. The urbanisation of our cities is no longer a reality that can be proven, claim the many studies looking into the issue. The periphery developed as a result of urban expansion, which allowed these cities to expand past the boundaries that colonisation left behind after independence.In this regard, it was considered worthwhile to present this paper that challenges the structure of the Algerian city using the example of the city of M’sila, which is located in the Hodna region and has a structural framework characterised by discontinuities and a spatial expansion. Moreover, typo-morphological; the term "suburbanization" has been used increasingly commonly to describe this tendency. The question of urban fragmentation is fundamentally raised by this type of "fragmented" urbanisation. The obvious question is: How are the cities distributed? Is the spread unified in both time and place?